Measuring Service Quality in Warung Pasta Bandung Using Servqual Method - Irsyam, Surya Ibrahim; Yudoko, Gatot (Journal of Business and Management, 2014)
Since 2010, the number of restaurants in Bandung has been growing. This makes the competition among restaurants potentially get more intense. Providing a good service to customers is very important for a restaurant that is in a very tight competition. Warung Pasta is one of the restaurants in Bandung that is in such competition. If Warung Pasta Bandung wants to succeed, it is necessary to provide quality service. The purpose of this research is to measure the service quality of Warung Pasta Bandung. One of the methods to measure service quality is the SERVQUAL method. There are five dimensions in SERVQUAL. With SERVQUAL method, the service quality of Warung Pasta Bandung is measured by calculating the difference between customers’ expectations and their perception (i.e. customer gap). By measuring the customer gap, it is possible to know the extent to which the customers are satisfied with the service provided by Warung Pasta Bandung. When the expectation score is higher than the perception score (i.e. negative gap), it means that the perceived service does not meet the customers’ expectations. But when the perception is higher than the expectation (i.e. positive gap), it means that the perceived service exceeds customers’ expectation. This research used survey to collect the data with the sample size of 280 respondents. Author also did pretest to 30 respondents in this research. Author used SPSS software to test the validity, reliability and also customer gap. The result shows that the gap for all dimensions is negative, indicating that the service at Warung Pasta Bandung does not seem to meet customers’ expectations.